Home or hospital for people with dementia and one or more other multimorbidities: What is the potential to reduce avoidable emergency admissions? The HOMEWARD Project Protocol. Issue 4 (3rd April 2017) - Voss, S; Black, S; Brandling, J; Buswell, M; Cheston, R; Cullum, S; Kirby, K; Purdy, S; Solway, C; Taylor, H; Benger, J
Abstract : Introduction: Older people with multimorbidities frequently access 999 ambulance services. When multimorbidities include dementia, the risk of ambulance use, accident and emergency (A&E) attendance and hospital admission are all increased, even when a condition is treatable in the community. People with dementia tend to do poorly in the acute hospital setting and hospital admission can result in adverse outcomes. This study aims to provide an evidence-based understanding of how older people living with dementia and other multimorbidities are using emergency ambulance services. It will also provide evidence of how paramedics make decisions about taking this group of patients to hospital, and what resources would allow them to make more person-focused decisions to enable optimal patient care. Methods and analysis: Phase 1: retrospective data analysis : quantitative analysis of ambulance service data will investigate: how often paramedics are called to older people with dementia; the amount of time paramedics spend on scene and the frequency with which these patients are transported to hospital. Phase 2: observational case studies : detailed case studies will be compiled using qualitative methods, including non-participant observation of paramedic decision-making, to understand why older people with multimorbidities including dementia are conveyed to A&E when they could be treated at home or in the community. Phase 3: needs analysis : nominal groups with paramedics will investigate and prioritise the resources that would allow emergency, urgent and out of hours care to be effectively delivered to these patients at home or in a community setting. Ethics and dissemination: Approval for the study has been obtained from the Health Research Authority (HRA) with National Health Service (NHS) Research Ethics Committee approval for phase 2 (16/NW/0803). The dissemination strategy will include publishing findings in appropriate journals, at conferences and in newsletters. We will pay particular attention to dissemination to the public, dementia organisations and ambulance services.